Tracking climatically suitable areas for an endemic Cerrado snake under climate change - Vasconcelos, Tiago da Silveira (Assoc Brasileira Ciencia Ecologica E Conservacao, 2014)
This study explores how climate change could potentially drive shifts in the geographic range of the Cerrado endemic snake Phalotris latiuittatus. By using three ecological niche modeling methods, I found that P. lativittatus is more likely to occur in the extent of its known geographic distribution (in Southeastern Brazil), but new distribution areas also include semideciduous forest southwestward from current occurrence points, as well as areas in the Cerrado and semideciduous forest northeastward of the current range. Niche models suggest that P. lativittatus would consistently reduce its total extent of occurrence through time. By 2050, the climatically suitable area for P. lativittatus is expected to be reduced by 65% to 70%, whereas the remaining range would reach only 10% to 20% of the current prediction by 2080. These predicted range contractions are associated with a southeastward range shift for predictions to 2050, while most of the predicted area to 2080 encompasses the same as that of 2050. (C) 2014 Associacao Brasileira de Ciencia Ecologica e Conservacao. Published by Elsevier Editora Ltda.
Keywords: Biodiversity hotspot; Dipsadinae; Ecological niche modeling